A hydrated phospholipid polymer-grafted layer prevents lipid-related oxidative degradation of cross-linked polyethylene. (January 2017) - Kyomoto, Masayuki; Moro, Toru; Yamane, Shihori; Takatori, Yoshio; Tanaka, Sakae; Ishihara, Kazuhiko
Abstract: The surface and substrate of a cross-linked polyethylene (CLPE) liner are designed to achieve resistance against oxidative degradation in the construction of hip joint replacements. In this study, we aimed to evaluate the oxidative degradation caused by lipid absorption of a highly hydrophilic nanometer-scaled thickness layer prepared by grafting a poly(2-methacryloyloxyethyl phosphorylcholine) (PMPC) layer and a high-dose gamma-ray irradiated CLPE with vitamin E blending (HD-CLPE[VE]). The HD-CLPE(VE) and PMPC-grafted HD-CLPE(VE) exhibited extremely high oxidation resistance regardless of lipid absorption, even though residual-free radical levels were detectable. The water wettability of the PMPC-grafted CLPE and PMPC-grafted HD-CLPE(VE) surfaces was considerably greater than that of untreated surfaces. The hydrated PMPC-grafted layer also exhibited extremely low solubility for squalene. Lipids such as squalene and cholesterol esters diminished the oxidation resistance of CLPE despite the vitamin E improvement. Notably, the PMPC-grafted surface was resistant to lipid absorption and diffusion as well as subsequent lipid-related oxidative degradation, likely because of the presence of the hydrated PMPC-grafted layer. Together, these results provide preliminary evidence that the resistance against lipid absorption and diffusion of a hydrated PMPC-grafted layer might positively affect the extent of resistance to the in vivo oxidation of orthopedic implants.